Identification of Soybean Genotypes in Wide Rows for Use in NClI'row-row Culture - Saleh, Ghizan; Griton, Earl T. (1988)
Thirty lines and six cultivars of soybeans (Glycine max (L.) Merr.) were evaluated in wide-row (76 em) and narrow-row (18 cm)spacingsat two locations in 1982 and one in 1983. The objective of the study was to determine if evaluation of lines in wide rows can be used to identify superior linesfor narrow-row culture. Yield in narrow rows was 27.0% higher than wide rows at both locations in 1982 and 20.8% higher in 1983. In general, the high yielding entries in wide rows were also the highest yielding ones in narrow rows, although they did not necessarily include all the highest yielding ones in narrow rows. One cultivar and two lines were, however, consistent in exhibiting a moderate to high response to narrowing of row spacing, over years and locations. No trait was identified as being associated with the response. In general, selection of lines superior in wide row nurseries will identify lines that will perform best in narrow-row culture.